Electronic spectroscopy of ethyl bromide probed by VUV photoabsorption and quantum chemical calculations. Issue 9 (15th February 2017) - Shastri, Aparna; Singh, Param Jeet; Krishnakumar, Sunanda; Das, Asim Kumar; Raja Sekhar, B. N.
Abstract : A comprehensive study of the electronic absorption spectra of C2 H5 Br and C2 D5 Br using synchrotron radiation photoabsorption spectroscopy and TDDFT calculations. Abstract : The electronically excited states of ethyl bromide and its deuterated isotopologue (C2 H5 Br and C2 D5 Br) are studied using synchrotron radiation based photoabsorption spectroscopy in the wavenumber region 50 000–86 000 cm −1 . A detailed spectral analysis supported by quantum chemical calculations is presented. A complex Rydberg series structure comprising of nsa 1, npa 1, npe, nda 1 and nde series, converging to each of the two spin–orbit split components of the first ionization potential ( 2 E3/2 and 2 E1/2 ) is observed for both the isotopologues. Quantum defect values are consistent with excitation from Br lone pair orbitals. Rydberg series analysis is extended to several higher members as compared to earlier work and corroborates the dominance of the spin–orbit mechanism over the hyperconjugative effect. A few new Rydberg series members converging to the second and third ionization potentials are observed and assigned. The complete gas phase VUV photoabsorption spectrum of C2 D5 Br up to its first ionization limit and its infrared absorption spectrum in the liquid phase are reported for the first time. An extended vibronic analysis of bands accompanying the first few Rydberg series is reported along with several new assignments. DFT calculations on ground states of neutral and ionic species and TDDFT calculations on singlet and triplet excited states aid and support the spectral analysis. Potential energy curves with respect to the C–Br bond length and the C–C–Br bond angle provide further insights into the nature of the excited states. This work represents a comprehensive study of the electronic absorption spectrum of ethyl bromide and its deuterated counterpart.